HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEBUGARAN JASMANI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Muhibbut Thibri; Tuti Restuastuti; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Physical fitness is a fundamental element being a human. A fit and healthy body helped us to maintain focus while studying, leads to excellent understanding and ability to solve a problem. This research aimed to discover the relationship of knowledge and attitude of faculty of medicine, university of riau students to their physical fitness level. This analytic research used a cross sectional design to 86 sample of faculty of medicine, university of riau students. This research used Harvard Step Test as the method to measure the fitness level and a valid questionnaire to assess the knowledge and attitude aspects. The result is 51 students (59.3 %) had a good knowledge, 46 students (53.5%) had a negative, and 71 students (82.6 %) had a bad physical fitness. From statistical point of view found p=1.031 for the relation between knowledge and physical fitness p=0.437 for the relation between attitude and physical fitness.Keywords: Knowledge, Attitude, Physical Fitness, Harvard Step Test